Dominikaner und Juden Personen, Konflikte und Perspektiven vom 13. bis 20. Jahrhundert = Dominicans and Jews : personalities, conflicts, and perspectives from the 13th to the 20th century - Füllenbach, Elias H. 1977-; Miletto, Gianfranco 1960- (Quellen und Forschungen zur Geschichte des Dominikanerordens, 2015)
This anthology examines the relationship between Dominicans and Jews from the beginnings of the religious order in the 13th century to the era of the Second World War. In addition to inquisitors and anti-Jewish sermonizers, the essays also present theologians and linguists from the Dominican order that engaged in lively cultural exchange with Jews and the Jewish tradition.